On rank tests for shift detection in time series - Roland Fried; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Robustified rank tests, applying a robust scale estimator, are investigated for reliable and fast shift detection in time series. The tests show good power for sufficiently large shifts, low false detection rates for Gaussian noise and high robustness against outliers. Wilcoxon scores in combination with a robust and efficient scale estimator achieve good performance in many situations.
Keywords: 519; signal extraction; jumps; outliers; test resistance